Chlorhexidine and Mupirocin for Clearance of Methicillin-Resistant Staphylococcus aureus Colonization After Hospital Discharge: A Secondary Analysis of the Changing Lives by Eradicating Antibiotic Resistance Trial. (31st May 2022) - Miller, Loren G; Singh, Raveena; Eells, Samantha J; Gillen, Daniel; McKinnell, James A; Park, Steven; Tjoa, Tom; Chang, Justin; Rashid, Syma; Macias-Gil, Raul; Heim, Lauren; Gombosev, Adrijana; et al.
Abstract: Background: The CLEAR Trial demonstrated that a multisite body decolonization regimen reduced post-discharge infection and hospitalization in methicillin-resistant Staphylococcus aureus (MRSA) carriers. Here, we describe decolonization efficacy. Methods: We performed a large, multicenter, randomized clinical trial of MRSA decolonization among adult patients after hospital discharge with MRSA infection or colonization. Participants were randomized 1:1 to either MRSA prevention education or education plus decolonization with topical chlorhexidine, oral chlorhexidine, and nasal mupirocin. Participants were swabbed in the nares, throat, axilla/groin, and wound (if applicable) at baseline and 1, 3, 6, and 9 months after randomization. The primary outcomes of this study are follow-up colonization differences between groups. Results: Among 2121 participants, 1058 were randomized to decolonization. By 1 month, MRSA colonization was lower in the decolonization group compared with the education-only group (odds ration [OR] = 0.44; 95% confidence interval [CI], .36–.54; P ≤ .001). A similar magnitude of reduction was seen in the nares (OR = 0.34; 95% CI, .27–.42; P < .001), throat (OR = 0.55; 95% CI, .42–.73; P < .001), and axilla/groin (OR = 0.57; 95% CI, .43–.75; P < .001). These differences persisted through month 9 except at the wound site, which had a relatively small sample size. Higher regimen adherence was associated with lower MRSA colonization ( P ≤ .01). Conclusions: In a randomized, clinical trial, a repeated post-discharge decolonization regimen for MRSA carriers reduced MRSA colonization overall and at multiple body sites. Higher treatment adherence was associated with greater reductions in MRSA colonization. Abstract : We examined microbiologic outcomes of the Changing Lives by Eradicating Antibiotic Resistance Trial, a large, randomized, multicenter, post-hospitalization decolonization clinical trial, and found that serial post-discharge decolonization with topical chlorhexidine, nasal mupirocin, and oral chlorhexidine significantly decreased methicillin-resistant Staphylococcus aureus colonization at key body sites for 9 months post-enrollment.